Conceptual Metaphor of Anger Emotion in Grunge Musicianâ€™s Song Lyrics - Febriansyah, Gema (Universitas Ahmad Dahlan, 2020)
This journal is entitled â€œConceptual Metaphor of Anger Emotion in Grunge Musicianâ€™s Song Lyricsâ€. The objective of this study is to analyze and describe conceptual metaphors of anger emotion that Grunge Musicians used in their song lyrics and to analyze and describe the image schema formed in conceptual metaphor of anger emotion. The data are taken from the lyrics of grunge musicians based on the Rolling stones magazine about the best grunge musicians all the time. The research uses a qualitative method since the data collected are in the form of words rather than numbers and it is conducted based on the conceptual metaphor theory and emotion concept theory from cognitive semantics study. The result of this research shows that the conceptual metaphor of anger emotion mostly used by grunge musicians are ANGER IS FIRE, ANGER IS AN OPPENENT IN A STRUGGLE, ANGER IS A NATURAL FORCE, and ANGER IS A HOT FLUID IN CONTAINER. The image schema that found in conceptual metaphor of anger emotion is FORCE SCHEMA and CONTAINMENT SCHEMA.